State-business relations: Ministries in business / Wan Juwairiah Nurbadrin Wan Ahmad Tajuddin - Wan Juwairiah Nurbadrin , Wan Ahmad Tajuddin (2021)
Malaysia practices a high level of state intervention. One method of such intervention is by employing government-linked companies (GLCs). However, it is still not widely known that Federal Ministries in Malaysia own and control GLCs. There were a total of 25 ministries in 2016, and each of them had ownership and control of GLCs. Other than that, the manner of corporate ownership by ministries varies as different ministries employ GLCs in different ways through different types of institutions. This has resulted in GLCs performing differently. This can be seen through case studies of ministries that own and control the largest number of GLCs. These ‘Big Four’ ministries, major players in the economy, are the Prime Minister's Department (PMD), Ministry of Finance (MoF), Ministry of Rural and Regional Development (MRRD) and Ministry of Science, Technology and Innovation (MOSTI). An assessment of the Big Four provides a clear view of how the government intervenes in the economy, and the implications of doing so in this manner. This study indicates that the employment of GLCs through the Big Four can be developmental or degenerative, based on the type of key institutions and key actors used when intervening in the economy. Different types of key actors and key institutions will result in different implications, socially, economically, and politically. The findings provide insights into the extent to which the government should intervene in the economy through the employment of GLCs under the jurisdiction of federal ministries in Malaysia.